2021
DOI: 10.1016/j.pedn.2020.07.003
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Parental Education on Screen Time, Sleep Disturbances, and Psychosocial Adaptation Among Asian Preschoolers: A Randomized Controlled Study

Abstract: Purpose: A recent increase in screen time during early childhood has adversely affected the sleep and psychosocial health of children; however, limited information is available regarding effective interventions to reduce the screen time among them. This study aimed to investigate the effect of a parental educational program on screen use, sleep quality, and psychosocial adaptation among preschoolers. Design and methods: A clustered randomized controlled study with a parallel-group design was conducted. Prescho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
0
10
2
1
Order By: Relevance
“…According to a randomized control study, conducted in Taiwan, when the screen time of children in experimental group was significantly reduced, they presented with improved sleep quality and attention score. 20 Strength: The information this study adds to the medical literature is that Education level of pre-schoolers is having significant association with screen time. Current study has also shown significant association with mother's employment status and screen time of pre-schoolers.…”
Section: Discussionmentioning
confidence: 87%
“…According to a randomized control study, conducted in Taiwan, when the screen time of children in experimental group was significantly reduced, they presented with improved sleep quality and attention score. 20 Strength: The information this study adds to the medical literature is that Education level of pre-schoolers is having significant association with screen time. Current study has also shown significant association with mother's employment status and screen time of pre-schoolers.…”
Section: Discussionmentioning
confidence: 87%
“…On the basis of cumulative evidence in this field [4,17,20,32,33,[37][38][39][40], the treatment approach used by the therapist in the current case studies encompasses three core elements: working with parents and families, individual therapy using CBT and motivational interviewing techniques, and focusing on IGD/ GD risk factors (e.g., social isolation, difficulties with self-control, impulsivity, family conflict, lack of warmth in family environment, low self-esteem and bullying [17]) and developmental domains (social, educational, behavioural and general health). Treatment is tailored to each child's symptoms and functioning, and relies on one parent at a minimum being willing to attend appointments and implement strategies at home.…”
Section: Clinical Approachmentioning
confidence: 99%
“…Studi terkontrol secara acak menunjukkan, bahwa setelah dilakukan intervensi program pendidikan orang tua yang mempunyai anak usia prasekolah tentang penggunaaan layar elektronik, kualitas tidur, serta psikososial anak berpotensi mengurangi waktu penggunaan layar pada anak, meningkatkan kualitas tidur dan adaptasi psikososial mereka (Lin et al, 2021). Marciano et al,(2020) mengungkapkan terdapat hubungan antara kerahasiaan dan pengungkapan diri dalam durasi penggunaan layar elektronik anak, sehingga perlunya orang tua dalam mendampingi dan mengawasi anak dalam menggunakan layar untuk membangun kepercayaan anak.…”
Section: Pengetahuan Orang Tuaunclassified